Quakerisme Dalam Film Dan Teater Amerika: The Triumphs Of Love (1795), The Quack Quakers (1916), Dan High Noon (1952) - Syofyan, Donny (Jurnal Ceteris Paribus, 2023)
Considering that Quakers have been used as important characters in American performance culture, this essay provides numerous examples of Quakers as represented in American theater and film: John Murdock’s play The Triumphs of Love (1795), Harry F. Millarde’s lost silent film The Quack Quakers (1916), and the Academy Award winning film High Noon (1952). In a paradoxical manner, in each of these productions ranging from farce to serious drama, Friends are shown as either claiming or as striving for unattainable moral and religious human ideals, but also as an exemplary community of individuals against which other Americans might and should be measured.